2020
DOI: 10.3390/molecules25245891
|View full text |Cite
|
Sign up to set email alerts
|

New Multifunctional Agents Based on Conjugates of 4-Amino-2,3-polymethylenequinoline and Butylated Hydroxytoluene for Alzheimer’s Disease Treatment

Abstract: New hybrids of 4-amino-2,3-polymethylenequinoline with different sizes of the aliphatic ring linked to butylated hydroxytoluene (BHT) by enaminoalkyl (7) or aminoalkyl (8) spacers were synthesized as potential multifunctional agents for Alzheimer’s disease (AD) treatment. All compounds were potent inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with selectivity toward BChE. Lead compound 8c, 2,6-di-tert-butyl-4-{[2-(7,8,9,10- tetrahydro-6H-cyclohepta[b]quinolin-11-ylamino)-ethylimino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 98 publications
0
42
0
Order By: Relevance
“…Inspired by the utility of phenolics in this challenging area, several small molecule inhibitors have also been reported in the literature. (Makhaeva et al, 2020) (Samanta et al 2019) Thus, it can be observed that there is a growing interest in exploring phenolics and phenolic based small molecules against a challenging disease like AD where there is a complicated interplay and interconnectivity of several biochemical pathways, which are involved in its progression and pathology. We can only hope that these potential phenolic molecules, with their multifunctional activities, would provide some therapeutic relief in an area such as AD therapy where there is an immense need for newer avenues of therapeutic modalities.…”
Section: Phadkementioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the utility of phenolics in this challenging area, several small molecule inhibitors have also been reported in the literature. (Makhaeva et al, 2020) (Samanta et al 2019) Thus, it can be observed that there is a growing interest in exploring phenolics and phenolic based small molecules against a challenging disease like AD where there is a complicated interplay and interconnectivity of several biochemical pathways, which are involved in its progression and pathology. We can only hope that these potential phenolic molecules, with their multifunctional activities, would provide some therapeutic relief in an area such as AD therapy where there is an immense need for newer avenues of therapeutic modalities.…”
Section: Phadkementioning
confidence: 99%
“…Inspired by the utility of phenolics in this challenging area, several small molecule inhibitors have also been reported in the literature. (Makhaeva et al., 2020) (Samanta et al. 2019) Thus, it can be observed that there is a growing interest in exploring phenolics and phenolic based small molecules against a challenging disease like AD where there is a complicated interplay and interconnectivity of several biochemical pathways, which are involved in its progression and pathology.…”
Section: A Note On Other Phenolic Molecules and Small Molecules Addressing The Multifaceted Toxicity Of Admentioning
confidence: 99%
“…Moreover, some studies have shown that BuChE may contribute to the pathogenesis of type 2 diabetes mellitus (T2DM) by causing insulin resistance; the latter is considered as one of the major risk factors contributing to AD onset [ 15 , 16 ]. Recently, several new structural scaffolds have been designed, synthesized, and studied as new cholinesterase inhibitors [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We now know that AChE can mediate functions that have a bearing on AD pathogenesis, namely, its peripheral anionic site (PAS) can bring about the aggregation of Aβ [ 24 , 25 , 26 ]. This finding has prompted a new research direction aimed at discovering drug candidates capable of both inhibiting AChE activity and its capacity to facilitate the formation of Aβ aggregates [ 27 , 28 , 29 , 30 , 31 , 32 ]. Agents possessing both these abilities could perform dual functions as cognition enhancers and disease modifiers [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These pathogenic features of ROS justify the incorporation of antioxidants in AD therapeutics [ 40 , 42 , 43 , 44 ]. Accordingly, in the search for potential therapeutic agents for AD, it could be beneficial to discover anticholinesterase compounds that could perform a double duty as antioxidants [ 32 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%